Unstimulated Salivary Flow Rate Corresponds with Severity of Xerostomia: Evaluation using Xerostomia Questionnaire and Groningen Radiotherapy-Induced Xerostomia Questionnaire - Shinta, Friendika DAI.; Dinar, Nushita; Susanto, Hendri; Agustina, Dewi (UI Scholars Hub, 2014)
One of the oral complications in head and neck radiotherapy is xerostomia. The severity of xerostomia can be observed using objective examination (unstimulated salivary flow rate measurement) and subjective examination (assessment using xerostomia questionnaires). There are two questionnaires used in assessment of xerostomia in head and neck cancer radiotherapy namely Xerostomia Questionnaire (XQ) and Groningen Radiotherapy-Induced Xerostomia Questionnaire (GRIX). Objective: To know the correlation between unstimulated salivary flow rate and severity of xerostomia assessment using two questionnaires. Methods: 30 head and neck cancer patients undergoing radiotherapy at Radiotherapy Department of RSUP Dr. Sardjito Yogyakarta between January-April 2013 were involved in this study. The assessment of xerostomia used xerostomia questionnaires (XQ and GRIX). Unstimulated salivary flow rate was measured in ml/minutes. Data was analyzed using Spearman Rank Correlation. Results: There is a negative significant correlation between salivary flow rate and severity of xerostomia with correlation coefficient -0.452 (p